Diversifikasi dan Optimalisasi Pengolahan Kulit Salak melalui Perlakuan Suhu dan Durasi Penyeduhan - Ni’matus Sholihah; Fadhil Muhammad Tarmidzi (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2022)
Salak is only used for the flesh of the fruit, for the peel and seeds of salak, it has not been widely developed into a product and only becomes waste. Consumption of peel is generally made in the form of extracts such as tea, where the peel is dried and then after drying it is mashed into powder and brewed using hot water. The use of hot water needs to attention to the temperature and brewing time because it can affect the amount of nutrient content in the peel tea. The temperature and brewing time affect the direct contact between water and the peel extract powder. The temperature used is 80,90,100 (oC) with a time of 5,7,10 (minutes). The analyzes carried out were analysis of raw material (moisture content), analysis of brewing quality, and chemical analysis (antioxidants, caffeine, tannins, and total sugar). The results showed that the best results were at 80oC for 10 minutes, the antioxidant content was 500.57 mg/ml, caffeine 0.65 mg/ml, tannins 1.35 mg/ml. The 80oC temperature treatment with a time of 7.5 minutes resulted in the highest total sugar content of 3.06%